Dampak persaingan geopolitik amerika serikat dan tiongkok terhadap posisi strategis indonesia di asia pasifik - Nugraheni, Ina (Maliki Interdisciplinary Journal, 2025)
The geopolitical rivalry between the United States and China in the Asia-Pacific region has intensified in recent years. As the largest archipelagic state located in the heart of the Indo-Pacific, Indonesia holds a strategic position directly impacted by the contest between these two major powers. This article analyzes the implications of the US–China rivalry on Indonesia’s strategic position, particularly in the domains of security, economy, and diplomacy. The findings indicate that this competition poses both challenges and opportunities for Indonesia. In terms of security, Indonesia faces growing pressure in the South China Sea and must enhance its maritime defense. Economically, Indonesia seeks to leverage the rivalry to attract investment and increase trade while maintaining economic autonomy. Diplomatically, Indonesia consistently upholds its independent and active foreign policy by “navigating between two reefs,” refusing to align with any bloc, and emphasizing ASEAN centrality. Through this approach, Indonesia aims to preserve its strategic autonomy and reinforce its role as a middle power contributing to regional stability.